Towards a Comprehensive Edition of the Arabic–Ethiopic Glossary of al-Malik al-Afḍal, Part II: New Readings from the Second Sheet - Bulakh, Maria; Kogan, Leonid (Aethiopica, 2014)
In Aethiopica 16, the first part of new readings from the al-Malik al-Afḍal’s 14th-century Arabic–Ethiopic Glossary was published. The present paper offers the results of analysis of the second sheet of the Glossary and contains all identifications which differ from those offered by Franz-Christof Muth. For the 53 entries from the second sheet of the Glossary, whose identification in Muth’s publication is either missing altogether or not sufficiently convincing, new readings are offered and discussed.